2004
DOI: 10.1002/app.20728
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial adhesion in model bioblends

Abstract: Model bioblends were investigated for interfacial adhesion using the asymmetric double cantilever beam (ADCB) fracture method. The model bioblends comprised two synthetic polymer components, one of which was the nonbiodegradable polymer polystyrene (PS). The second component was a synthetic biodegradable polyester, which was either polycaprolactone (PCL) or Eastar Bio Copolyester® (EBU). The critical strain energy release rate (G Ic ) data from the ADCB fracture experiments on the model bioblends decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…PCL has been blended with WG,8 starch,10–15 corn zein,16, 17 wood flour/lignin,18 and soy protein 19. In general, PCL filled with starch, corn zein, or wood flour/lignin loses tensile strength in a linear fashion 10–18. PCL has also been blended with cellulose fibers, which reinforce composites similarly to glass fibers 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…PCL has been blended with WG,8 starch,10–15 corn zein,16, 17 wood flour/lignin,18 and soy protein 19. In general, PCL filled with starch, corn zein, or wood flour/lignin loses tensile strength in a linear fashion 10–18. PCL has also been blended with cellulose fibers, which reinforce composites similarly to glass fibers 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…Also at 50 wt % Novatein, the interfacial area is much greater (co‐continuous phase), which serve as heterogeneous nucleation sites. According to classical nucleation theory, the surface free energy at heterogeneous nucleation sites is lower leading to the observation that at equal proportions of Novatein and PLA a larger number of nano‐cells formed. At higher Novatein contents (above 50 wt %), it was difficult to obtain a cellular structure upon foaming (results not shown) because of a high matrix stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…1 Biodegradable binary blends of PS with degradable polymers such as polycaprolactone and poly(lactic acid) (PLA) were investigated. 2 It was found that PS/PLA composites exhibited better mechanical properties when compared with other fillers used. However, a blend of PS with a biopolymer is incompatible owing to their inherent structural differences.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, starch/synthetic polymer blends containing 70% starch was prepared by Ramaswamy and Bhattacharya 1. Biodegradable binary blends of PS with degradable polymers such as polycaprolactone and poly(lactic acid) (PLA) were investigated 2. It was found that PS/PLA composites exhibited better mechanical properties when compared with other fillers used.…”
Section: Introductionmentioning
confidence: 99%